Re-validation of the Kenny Music Performance Anxiety Inventory-revised among Chinese university students majoring in vocal music - Pan, Li; Chen, Qihuan; Lou, Lan; Gu, Qizhen; Luo, Huiqin; Li, Ping; Liu, Yannan (Frontiers in Psychology, 2025)
IntroductionDue to its significant impact on performers’ psychological well-being and career development, music performance anxiety (MPA) has recently received growing public attention. The Kenny Music Performance Anxiety Inventory-Revised (K-MPAI-R) is one of the most widely focused MPA scales, often used to assess the manifestations and influencing factors of MPA in musicians across different genres and professional stages. However, most current K-MPAI-R validation studies did not distinguish between vocal and instrumental performers. As they differ significantly in performance settings and stressors, these variations may impact the validity of the scale and lead to biased results.MethodsWith Kenny’s permission, this study aims to re-examine the reliability and validity of the K-MPAI-R in the context of Chinese university students majoring in vocal music. 736 Chinese students participated in this study. The researchers divided the total sample into two equal subsamples, each consisting of 368 students. One subsample was subjected to exploratory factor analysis (EFA) and the other to confirmatory factor analysis (CFA).ResultsThrough EFA, the researchers obtained a four-factor model (F1: Psychological Vulnerability, F2: Proximal Somatic and Cognitive Anxiety, F3: Parental Support, F4: Memory Self-Efficacy); subsequently, CFA was employed to confirm that the model demonstrated a good fit and exhibited adequate reliability and validity.DiscussionThis study represents the first refined validation of the K-MPAI-R scale for Chinese university students majoring in vocal music, providing cross-cultural and discipline-specific evidence for optimizing measurement tools to assess MPA among vocal performers accurately.